Exploration of the relationship between stigma and burnout among Greek nurses in dementia care. (10th March 2020) - Mantzorou, Marianna; Economou, Marina; Kalokerinou, Athena; Sourtzi, Panayota; Zyga, Sofia; Politis, Antonis; Koukia, Evmorfia
Abstract: Objective: To investigate possible correlations between stigma and burnout of nurses and non‐graduate professional caregivers of elderly with dementia in nursing homes. Background: Research on dementia stigma in health care professionals as well as its relationship with their well‐being is seriously lacking. Methods: This cross‐sectional study involved a convenience sample of 171 nurses and other professional caregivers in 16 Greek elderly care units who responded to Maslah Burnout Inventory (ΜΒΙ) as well as the Family Stigma in Alzheimer's Disease Scale (FS‐ADS). In order to find adjusted associations between independent variables and the stigma and burnout of professional caregivers, multiple linear regression analysis was used. Results: Cognitive, emotional and behavioural attributions of the three dimensions of stigma were found to be independent predictive factors of burnout's dimensions which indicate that stigma nurses deposit on patients, contributes towards their burnout. Conclusion: Educational preparation of geriatric nurses should provide them with the option of seeing dementia as a normal stage of life since reducing stigma can contribute towards preventing and managing professional burnout. Implications for Nursing Management: In order to reduce burnout, nurse managers should design lifelong learning programs on the basis of changing the stigmatizing negative cognitive and emotional attitudes of professionals towards dementia.